2020
DOI: 10.3390/ijerph17155459
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptance of Key Public Health Interventions by the Polish Population Is Related to Health Literacy, But Not eHealth Literacy

Abstract: Background: Public health and health promotion rely on many different interventions, which range from health education and communication, through community mobilisation and changes to environmental conditions, to legal and fiscal actions. The introduction of the increased tax on sugar-sweetened beverages (SSB), popularly called sugar tax (ST), and a mandatory programme of vaccinations are the strategies inciting the most vivid discussions in Polish society. The study was intended to assess the determinants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…They did not find a statistically significant relationship between eHL and the level of anxiety, neither among older persons from the USA nor from South Korea [94]. It should be added that an earlier study performed in a representative sample of the Polish population suggested that attitudes to key public health interventions were related to the level of HL but not eHL (measured with Pl-eHEALS) [95]. Furthermore, eHL was not a significant predictor of the quality of telehealth experience during the COVID-19 pandemic in the sample of patients from Australia [96].…”
Section: Discussionmentioning
confidence: 91%
“…They did not find a statistically significant relationship between eHL and the level of anxiety, neither among older persons from the USA nor from South Korea [94]. It should be added that an earlier study performed in a representative sample of the Polish population suggested that attitudes to key public health interventions were related to the level of HL but not eHL (measured with Pl-eHEALS) [95]. Furthermore, eHL was not a significant predictor of the quality of telehealth experience during the COVID-19 pandemic in the sample of patients from Australia [96].…”
Section: Discussionmentioning
confidence: 91%
“…Our analysis showed that only 32% of respondents supported the statement that a tax on SSBs is an appropriate measure to counteract the obesity epidemic, and 46% did not agree. Interestingly, a telephone-based survey performed in 2016 among Polish adults showed a very similar distribution of responses to this item: 37.3% supported the introduction of a tax on SSBs, and 40.2% did not [53]. Low acceptance of fiscal intervention may depend on several factors.…”
Section: Discussionmentioning
confidence: 95%
“…Regardless, factors associated with attitudes towards vaccination differ across countries [ 37 ], while data on public attitudes towards vaccination in Poland remains inconsistent. In 2016, Duplaga [ 38 ] studied a representative sample of Poland's adult inhabitants and reported that individuals who had higher education, were married, as opposed to single, and were currently employed were more likely to declare trust in vaccine safety and effectiveness. Braczkowska et al [ 39 ] showed that perceived risk of adverse vaccine reaction (AVR), contraindications and perception of the qualification procedure for vaccination as substandard were significant factors associated with the rating of children's vaccination as unsafe.…”
Section: Discussionmentioning
confidence: 99%